Une nouvelle méthode de quantification des réactions périostées en paléopathologie : l’indice pondéré d’atteinte périostée (IPAP) - Micheline Lé; Yann Ardagna; Silvia Bello; Olivier Dutour (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
In order to evaluate the level of periosteal reaction on an isolated bone, an affected individual or an ancient population, we propose a new quantification method, taking into account simultaneously (i) the degree of periosteal reaction (Periosteal Reaction Stage, PRS), (ii) the degree of anatomical preservation and representation (Anatomical Preservation Index, API) and (iii) the state of preservation of the cortical surface (Qualitative Bone Index, QBI) of each bone segment. The “Periosteal Pattern Weighed Index” corresponds to the following formula PPWI = (Σ PRS/ OSN) x FQ x FK where OSN represents the number of segments for which the API, the QBI or the PRS are observable, FQ corresponds to the quantity factor and FK is a factor weighing the state of cortical surface preservation. This formula has been tested on several human osteoarchaeological samples with good reproductibility (intra and inter- observer). The results of the application of this new index to these samples and its potential application as a palaeoepidemiological marker are presented in this paper.